The impact of task-based instruction program on fostering ESL learners' speaking ability: a cognitive approach - Mohammadipour, Mohammad; Md. Rashid, Sabariah (Australian International Academic Centre (AIAC), 2015)
Adopting a direct approach to contrive sufficient focus on form (accuracy) would facilitate interlanguage development without decreasing the naturalness of communication that communicative tasks can generate. This study aimed to determine the effectiveness of a proposed task-based instruction programme within a cognitive approach in fostering overall speaking proficiency of undergraduate students. 72 students from several public universities participated in the study, which employed an experimental design. The students of the experimental group received training through the proposed task-based instruction programme for three months while those in the control group received regular instruction. The preliminary English Test (PET) was administered as a pre- and post-test measure of speaking proficiency. Findings of the study showed a significant improvement in the overall speaking proficiency of the students who were exposed to the proposed programme. The findings suggest the potential of the task-based programme in enhancing undergraduate students' overall speaking proficiency.